Pemberdayaan Komoditas Rumput Laut “Algae” dan Perubahan Sosial Ekonomi Warga Desa di Pesisir Pantai Bentenan Kabupaten Minahasa Selatan - Rompis, Deitje (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
The business utilization however affects social and economics’ component for the community lives.  This was shown by the study for seaweed production over the enhances to design the factors of utilization component as it affects to the social-economic factors of the households.  Utilization component was comprised of the factors of, financing, raw materials (seeds for seaweed and tools), plantation and maintaining, reaping and storing, marketing and the government assistance.  The forgoing factors were considered as variables for the study, that observed individually and collectively towards the social-economic factors.  Such social-economic factors that considered as research variables, were, the congregational concern, communion, infrastructures, environment, educational level, health care, earnings, consumption, savings and investments.  By the usage of interview and questionnaire, as research instrument with the total population N=40, the researcher specify the results of the study as following.  The reaping and storing variable in general related to utilizing component in average value 4.475, standard deviation 0.056.  However environment variable as well as the health level, respectively attained in value of 4.474 and 4.525, standard deviation 0.506 and 0.554, while towards saving 4.450 and investment 4.425, and standard deviation respectively 0.504 and 0.549.  The result of Pearson product moment correlation noted that the value of financial variable towards the importance of plantation technology and the maintaining of the process of seaweed as r=0.59676.  On the other hand, with regards to the variable for reaping and storing seaweed products as r=0.6985, while for the final processing r=04612 and towards the developments for the marketing link as r=0.6985, while for the final processing r=04612 and towards the developments for the marketing link as r=0.3411.  The four matrix relationship were surpassing the relationship value as it based on the 95% significant level in degree of freedom 39, which stated to reject the null  hypotheses.  The study found that the increasing of real earnings of the households, after four (4) years period engaging the seaweed household business.  That among thirty-one (31) respondents stated their changes in earnings of 186% from their earlier earnings annually Rp. 5.2 millions to Rp 33.6 millions.  Probably to utilize the household business of seaweed in Bentenan affects their social-economics component.